The future of rongoa Maori: wellbeing and sustainability. - Ahuriri-Driscoll, A.; Baker, V.; Hepi, M.; Hudson, M.; Mika, C.; Tiakiwai, S. (2008)
Rongoa Maori is a holistic system of healing that has developed out of Maori cultural traditions. It has a long history of usage and credibility among Maori, and increased interest in its revival and sustainability has prompted calls for its formalisation within the New Zealand public health system. Objective and methods The objectives of the research project were to: - Examine the contribution of rongoa Maori to indigenous wellbeing, and - Identify issues for the ongoing sustainability of traditional Maori healing in New Zealand. The research process was lead by Maori researchers in collaboration with Maori healers and stakeholders. Two literature reviews were undertaken; one to provide understanding of international developments in traditional medicine, and a second to review national policy/literature related to rongoa Maori. Four focus groups and five workshops were held with groups in five communities to explore current rongoa practice and service delivery and drivers/barriers to its ongoing utilisation. The participant groups were healers and their associates, and health and local authority stakeholders.
Keywords: hauora; health; rongoa

The politics and practice of counting: Ethnicity in official statistics in Aotearoa/New Zealand - Cormack, Donna (Te Rōpū Rangahau Hauora a Eru Pōmare, 2010)
The politics and practice of counting: ethnicity in official statistics in Aotearoa/New Zealand was produced as part of a broader project funded by Te Kete Hauora, Ministry of Health to investigate issues with ethnicity data in New Zealand and the implications of these for the Māori health and disability sector. The paper is one in a series of topic-based discussion papers. It aims to summarise key literature on the measurement of the Māori population in official ethnic statistics over time as a background to the accompanying discussion papers.
Keywords: crown policy; ethnic identity; ethnicity; health; health outcomes; identity; policy; statistics